(untitled) (Scientific journal of the Fergana State University, 2025)
This article studies in detail the chemical elemental composition of cultivated plants-phytomeliorants growing on saline lands, with water-soluble salts from which the plant receives toxic and non-toxic elements of substances that migrate into plant-animal-human chains, the geochemical characteristics of which are described on the basis of log-normal spectra, studied chemical elements. In addition, the medicinal and phytoremedial properties of the Solanum nigrum plant are discussed in detail.